2008
DOI: 10.1021/om700945r
|View full text |Cite
|
Sign up to set email alerts
|

New Rare Earth Metal Bis(alkyl)s Bearing an Iminophosphonamido Ligand. Synthesis and Catalysis toward Highly 3,4-Selective Polymerization of Isoprene

Abstract: Newrareearthmetalbis(alkyl)complexes[(NPN Ph )Ln(CH 2 SiMe 3 ) 2 (THF)](NPN Ph :N(Ph)PPh 2 dNC 6 H 2 Me 3 -2,4,6; Ln ) Sc (3a), Ln ) Y (3b), Ln ) Lu (3c)) and [(NPN Py )Sc(CH 2 SiMe 3 ) 2 (THF)] (NPN Py ) N(Py)PPh 2 dNC 6 H 2 Me 3 -2,4,6) (3d)) have been prepared via protonolysis reaction between rare earth metal tris(alkyl)s and the corresponding iminophosphonamines. Complexes 3a-d are analogous monomers of THF solvate. Each metal ion coordinates to a η 2 -chelated NPN ligand and two cis-located alkyl groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 63 publications
7
42
1
Order By: Relevance
“…However, the chemistry of transition metal iminophosphonamides (NPN) that had been considered to be heteratomic analogs of the corresponding metal amidinates has been developing slowly. Nevertheless, in the last two decades transition metal iminophosphonamides have been reported as active catalysts for alkene polymerization (NiNPN, ZrNPN), 3,4‐selective polymerization of isoprene (rare earth NPN complexes), alkene oligomerization (CrNPN), ethene dimerization (NiNPN),[5c] cyclopropanation and aziridination (CuNPN), as well as for Tsuji–Trost cross‐coupling (PdN 2 P) Recently we have demonstrated that arene ruthenium iminophosphonamide [( p ‐cymene)RuCl{Ph 2 P(N‐ p Tol) 2 }] can efficiently reduce acetophenone under transfer hydrogenation conditions …”
Section: Introductionmentioning
confidence: 99%
“…However, the chemistry of transition metal iminophosphonamides (NPN) that had been considered to be heteratomic analogs of the corresponding metal amidinates has been developing slowly. Nevertheless, in the last two decades transition metal iminophosphonamides have been reported as active catalysts for alkene polymerization (NiNPN, ZrNPN), 3,4‐selective polymerization of isoprene (rare earth NPN complexes), alkene oligomerization (CrNPN), ethene dimerization (NiNPN),[5c] cyclopropanation and aziridination (CuNPN), as well as for Tsuji–Trost cross‐coupling (PdN 2 P) Recently we have demonstrated that arene ruthenium iminophosphonamide [( p ‐cymene)RuCl{Ph 2 P(N‐ p Tol) 2 }] can efficiently reduce acetophenone under transfer hydrogenation conditions …”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported the cis −1,4 polymerization of the monomer MHD, showing the potential orthogonal reactivity of the two reactive sites in coordination polymerization . To obtain 1,2‐PMHD, we refer to the catalyst systems active for the 3,4‐regioselective polymerization of isoprene, which are relatively limited . In addition, we have to screen out those active for ethylene or α ‐olefin polymerization, leaving few room for choice.…”
Section: Resultsmentioning
confidence: 99%
“…The aminophosphinimido dialkyl scandium complex 107 Sc reported by Cui and co‐workers in combination with [PhNHMe 2 ][B(C 6 F 5 ) 4 ] and Al i Bu 3 formed the first non‐Cp‐ligated rare‐earth metal based catalytic system providing extremely high activities and 3,4‐selectivities for the IP polymerization . Sequentially, a variety of rare‐earth metal bis(alkyl) complexes 107 Lu – 116 featuring NPN ligands developed by same group also displayed highly activities and 3,4‐seletivities for IP polymerization (Figure ) .…”
Section: Stereoselective Polymerization Of Conjugated Dienesmentioning
confidence: 99%